Pertunjukan Teater Karo Hip Hop Kontemporer KAI - Silvia Anggreni Purba (Institut Seni Indonesia Yogyakarta, 2012)
Pertunjukan ini berawal dari sebuah ide untuk mengkolaborasikan tradisi Karo dengan budaya populer. Dengan cara seperti ini pertunjukan bisa dinikmati tanpa batasan bahasa dan budaya. Proses menggabungkan dua budaya yang berbeda merupakan bentuk budaya hibrida dan terjadi akibat proses globalisasi. Melalui proses pengendapan pengamatan dan kesan yang kuat, pertunjukan ini dibawa ke dalam bentuk Hip Hop. Pertunjukan ini merupakan bagian dari sebuah tragedi modern dengan karakter destruktif, mengeksplorasi emosi dan menyampaikannya kepada penonton. Eksplorasi budaya Karo dan tari Hip Hop sebagai bahasa simbol mampu memperkuat kata-kata. Gerak tidak diungkapkan dengan kata lisan tetapi disajikan melalui gerak tari Hip Hop. Penafsiran legenda dan teks ke dalam gerak, melalui proses pelatihan di laboratorium sebagai proses pencarian dan eksperimentasi diwujudkan dengan mempertimbangkan unsur-unsur dasar dari Hip Hop, unsur budaya Karo dan tontonan. Karo Hip Hop diharapkan menjadi bentuk estetika teater modern yang diinginkan tanpa kehilangan tradisi.Kata kunci: Tari Karo kontemporer, Hip-hop, budaya hibridaABSTRACTPertunjukan Teater Karo Hip Hop Kontemporer KAI. The performance of Karo Theater collaborated with Hip Hop stems from a simple idea to collaborate Karo cultural traditions with popular culture. The performances can be enjoyed without having limitation on the language and culture. The process of combining two different cultures is a form of hybrid culture, and it may occur due to the globalization process. Through the process of deposition of the observations and strong impression, this performance is then brought into the form of Hip Hop as a preferred form which is energetic, personal and global. This performance is part of a modern tragedy with its destructive character which has explored the emotion and has presented it to the audiences. The exploration of Karo cultural tradition and Hip Hop dance as a language of symbols is able to reinforce words. The movement is not revealed by the verbal phrase but is presented through the movement of Hip Hop dance. The interpretation of the legend and texts into movement is carried out through the training process at the laboratory as a searching process and experiment, and afterward can be realized by considering the basic elements of Hip Hop, Karo cultural elements and performance. Karo Hip Hop Theatre is expected to become a preferred aesthetic form of a modern theater without losing its tradition form.Keyword: a contemporary Karo theater, Hip Hop, hybrid culture.